I am brave - Capozzi, Suzy; Unten, Eren Blanquet (New York, NY : Rodale Kids, an imprint of Rodale Books, 2018)
On a family vacation a young girl shows bravery by trying new experiences, including surfing, horseback riding, and hiking.
400
Keywords: Bravery; Courage -- Juvenile fiction; Conduct of life -- Juvenile fiction; Picture books; Courage -- Fiction; Behavior -- Fiction; Picture books; JUVENILE FICTION -- Reader -- Beginner; JUVENILE FICTION -- Social Themes -- Emotions & Feelings; JUVENILE FICTION -- Social Themes -- Self-Esteem & Self-Reliance.; JUVENILE FICTION -- Social Themes -- Values & Virtues; JUVENILE FICTION / Readers / Beginner; Readers (Publications).